Good manufacturing practice in low‐ and middle‐income countries: Challenges and solutions for compliance - Pelden Chejor; Thinley Dorji; Ngawang Dema; Andrew Stafford (Wiley, 2024)
Abstract Approximately 2 billion people globally have limited access to essential medicines, particularly those living in low‐ and middle‐income countries (LMICs). In addition, there is a higher prevalence of substandard and counterfeit medicines in LMICs, which may cause antimicrobial resistance and therapeutic failure. Good manufacturing practice (GMP) is key to ensuring access to high‐quality, safe and effective medicines, including active pharmaceutical ingredients and excipients used for manufacturing finished dosage forms. Compliance with GMP standards saves resources for both manufacturers (e.g. avoiding expensive product recalls) and governments (e.g. minimising compliance inspections). Concerted collaborations among different countries to harmonise GMP standards and procedures have occurred, and the World Health Organisation (WHO) GMP is commonly used in LMICs. However, barriers to GMP compliance remain apparent, particularly in LMICs. Pharmaceutical manufacturers in LMICs face several barriers such as inadequate resources and infrastructure, inefficient or weak regulation, a shortage of skilled people and limited training opportunities for manufacturing personnel. Although national regulatory authorities (NRAs) have been established in LMICs, most NRAs are not fully independent and are placed within the health department. NRAs in LMICs are not able to fully utilise international and regional reliance mechanisms and collaborations. Therefore, both NRAs and pharmaceutical manufacturers must be adequately supported through resources, infrastructure and capacity‐building opportunities. NRAs must be suitably empowered with assured functional independence. A comprehensive guideline for managing conflicts of interest among pharmaceutical manufacturers, procurement agencies and NRAs is needed. NRAs must liaise with other NRAs, participate in joint GMP inspections and leverage the expertise of regional or international collaborations. Pharmaceutical manufacturers in LMICs can leverage WHO GMP standards to improve GMP compliance and expand their market. However, as these solutions may have cost implications, prioritising key gaps for GMP compliance and optimisation of available resources are essential.